Pengembangan Sistem Informasi Manajemen Aset Fakultas Ilmu Komputer Universitas Brawijaya berbasis Mobile - Umar Zaki Izzuddin; Herman Tolle; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Faculty of Computer Science (FILKOM) has a work unit that is responsible for managing and maintaining infrastructure, namely the general and equipment work units. There are several problems that exist in this work unit. The first problem is that the process of reporting complaints from the academic community is still verbal so that it takes time to coordinate from the reporter to the staff of the infrastructure section until the improvement of infrastructure is carried out. The second problem is that the process of making daily activity reports made in the form of physical documents results in wasteful use of paper and file stacking. The third problem is in routine maintenance activities, making maintenance reports from activities already use google forms but there is a buildup of data on the limited capacity of the google drive. From the use of this google form, there are also problems in the form of incomplete maintenance data and mismatch of data from each infrastructure. This research seeks to develop a mobile-based asset management information system. This research adopts the waterfall method in system development. The stages of the waterfall method are requirements, design, implementation and testing. The requirements stage produced four actors, 28 functional needs, one functional need, and requirements modeling using use case diagrams and use case scenarios. Design stage results in modeling sequence diagrams, diagram classes, algorithm design, database design and interface design. The implementation stage is carried out by realizing the actual system of the results of the design that has been carried out. All functional requirements tests which are unit testing, integration testing, and validation testing result in valid status in all test cases. In the usability test, an average score of 87,5 was obtained, which means that the system is acceptable to users.